PENGARUH KOMPENSASI EKSEKUTIF DAN KARAKTER EKSEKUTIF TERHADAP PENGHIDARAN PAJAK (TAX AVOIDANCE) PADA PERUSAHAAN PROPERTY,REAL ESTATE, DAN BUILDING CONSTRUCTION YANG TERDAFTAR DI BEI - Sahril Syahruddin; Muh Suun; Darwis Lannai (Universitas Muhammadiyah Makassar, 2020)
This study examined the influence of executive compensation and executive character on the tax avoidance. Sample of this research was property, real estate and building construction industry which is listed in Indonesian Stock Exchanges during 2014-2018. This research used purposive sampling method, the number of property, real estate and building construction that were became 19 companies with 5 years observation. Hypothesis in these research were tested by multiple regression model. The result of this research showed that (1) Executive compensation has a significant effect on tax avoidance. (2) The executive character has a significant effect on tax avoidance.